Application of Culturally Responsive Teaching Approach Assisted by Padlet Media of Traditional Game Materials to Improve Student Learning Outcomes - Triwahyudianto, Triwahyudianto; Susanti, Suci Indah; Suprapti, Dhia (Pedagogi : Jurnal Pendidikan dan Pembelajaran, 2025)
This research aims to improve student learning outcomes in the Pancasila Education subject of Traditional Game materials through the application of the Culturally Responsive Teaching (CRT) approach assisted by Padlet digital media. The background of this research is that there is still low student learning outcomes due to conventional learning methods that are less relevant to the local cultural context and the lack of use of interactive digital media in learning Pancasila Education in elementary schools. This research fills the gap in the study on the integration of CRT with Padlet media in Pancasila Education materials at the elementary level. The method used is the Kemmis & McTaggart model Class Action Research, carried out in two cycles which each consist of planning, action, observation, and reflection stages with 28 subjects in grade III of Bandungrejosari 2 Malang Public Elementary School. The research instruments include teaching modules, Padlet media, Student Worksheet, and evaluation tests. The results showed an increase in student learning completeness from 28% in the pre-cycle (average 45), to 57% in the first cycle (average 67), and a significant increase to 78% in the second cycle (average 80). These findings show that the application of the CRT approach assisted by Padlet digital media is effective in improving student learning outcomes. The implications of this study support the importance of using local culture-based digital media in learning Pancasila Education in the Merdeka curriculum to create a more contextual, interactive, and meaningful learning experience.